(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Based on Performance Studies in Education, this investigation sought to understand some meanings of the notion of student in performance through an experience with dance in Art classes in a public elementary school. From the analysis of an audiovisual work produced during that experience, a school ritual was observed that, based on control symbols, is subverted by students in performance who constantly reconfigure their orders. When entering social performances in the school space, students began to tension their subject positions, making it necessary, therefore, to have a greater attachment to the body, whose dance became a concern about more (un)schooled performative practices.